Differential Regulation of PI(4,5)P2 Sensitivity of Kv7.2 and Kv7.3 Channels by Calmodulin - Gomis-Perez, Carolina; Soldovieri, Maria V.; Malo, Covadonga; Ambrosino, Paolo; Taglialatela, Maurizio; Areso, Pilar; Villarroel, Alvaro (Frontiers in Molecular Neuroscience, 2017)
The identification and understanding of critical factors regulating M-current functional density, whose main components are Kv7.2 and Kv7.3 subunits, has profound pathophysiological impact as a result of the important role of the M-current on neuronal excitability control. We report the increase in current density of Kv7.2 channels by calmodulin (CaM) and by a mutant CaM unable to bind Ca2+ (CaM1234) revealing that this potentiation is calcium independent. Furthermore, after co-expressing a CaM binding protein (CaM sponge) to reduce CaM cellular availability, Kv7.2 current density was reduced. Current inhibition after transient depletion of the essential Kv7 co-factor phosphatidylinositol-4,5-bisphosphate (PI(4,5)P2) by activating Danio Rerio voltage sensitive phosphatase (DrVSP) was blunted by co-expressing CaM1234 or the CaM sponge. In addition, CaM-dependent potentiation was occluded by tonic elevation of PI(4,5)P2 levels by PI(4)P5-kinase (PIP5K) expression. In contrast to the effect on homomeric Kv7.2 channels, CaM1234 failed to potentiate heteromeric Kv7.2/3 or homomeric Kv7.3 channels. Sensitivity to PI(4,5)P2 depletion of Kv7.2/3 channels was increased after expression of CaM1234 or the CaM sponge, while that of homomeric Kv7.3 was unaltered. Altogether, the data reveal that apo-CaM influences PI(4,5)P2 dependence of Kv7.2, Kv7.2/3, and of Kv7. 3 channels in a subunit specific manner.